2014
DOI: 10.1186/s11568-014-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide pattern of population structure and admixture in peninsular Malaysia Malays

Abstract: Background: The Malays consist of various sub-ethnic groups which are believed to have different ancestral origins based on their migrations centuries ago. The sub-ethnic groups can be divided based on the region they inhabit; the northern (Melayu Kedah and Melayu Kelantan), western (Melayu Minang) and southern parts (Melayu Bugis and Melayu Jawa) of Peninsular Malaysia. We analyzed 54,794 autosomal single nucleotide polymorphisms (SNPs) which were shared by 472 unrelated individuals from 17 populations to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…In addition to that, the F ST between the north and south Malays were similar to those of the earlier report between the northern and southern Han Chinese (F ST = 0.0011) [ 12 ] but lower than those within Europeans (F ST = 0.0033) [ 14 ] However, we observed higher diversity within the substructures of the Malays. For instance, the F ST between two northern Peninsular Malays from Kedah and Kelantan was 0.017 (Table S4), which is in line with the finding in a recent study [ 4 ]. This suggests higher heterogeneity among Malays than previously expected, possibly be due to the recent migration and gene flow from the surrounding populations in this region.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to that, the F ST between the north and south Malays were similar to those of the earlier report between the northern and southern Han Chinese (F ST = 0.0011) [ 12 ] but lower than those within Europeans (F ST = 0.0033) [ 14 ] However, we observed higher diversity within the substructures of the Malays. For instance, the F ST between two northern Peninsular Malays from Kedah and Kelantan was 0.017 (Table S4), which is in line with the finding in a recent study [ 4 ]. This suggests higher heterogeneity among Malays than previously expected, possibly be due to the recent migration and gene flow from the surrounding populations in this region.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies had indicated potential genetic sub-structure among the different groups of Malays from Peninsular Malaysia [ 2 , 4 , 5 ], which could be possibly attributed to the migration history of these respective sub-groups. However, fine-scale sub-structure of the Malay population remained poorly described, especially, previous studies were based on very limited sample size.…”
Section: Introductionmentioning
confidence: 99%
“…We show that Brunei Chinese were equally distant from Malaysia Singapore, Taiwan, and Hong Kong Chinese, this could be explained by migration and ethnical crossbreeding or admixture of the Brunei Chinese population .…”
Section: Discussionmentioning
confidence: 72%
“…In Malaysia, the proportion of known diabetes is estimated to have increased from 6.5 to 9.5%, accompanied by a three-fold enlargement in newly diagnosed cases from 1.8 to 5.4% over the same period (Letchuman et al, 2010;Etemad et al, 2013;Haghvirdizadeh, et al, 2015). Malaysia has different subethnic groups (Hatin et al, 2014). In 2011, an identical trend was observed, in which the total Malaysian diabetes population, consisting of known and newly diagnosed cases, increased from 11.7 to 13.3% by 2030 (Whiting et al, 2011).…”
Section: Introductionmentioning
confidence: 99%